Identification of a gene that regulates expression of M protein, the major virulence determinant of group A streptococci. - Caparon, M G (1987)
By using Tn916 insertional mutagenesis, we have identified mry (M protein RNA yield), a gene required for high-level expression of the M protein, an essential virulence determinant of the group A streptococcus. The mry::Tn916 mutation causes a reduction by a factor of approximately equal to 50 in the amount of M protein produced, in the original strain and in a nonmutagenized host to which the mutation was transferred by transduction. The insertion is located approximately 1.8 kilobases upstream of the structural gene for M protein (emm) and its promoter. The genomic region including mry::Tn916 and emm was cloned on a cosmid vector and introduced into Escherichia coli. When the transposon excised precisely from the chimeric cosmid in E. coli, the resulting streptococcal DNA showed the same restriction pattern as the homologous chromosomal region in the parental nonmutagenized streptococcus. The sequence of the promoter for emm was not altered in the mry mutant. The reduction in protein correlates with a decrease in the amount of M protein-specific mRNA, indicating that mry regulates transcription of emm.